2021
DOI: 10.1016/j.coesh.2021.100296
|View full text |Cite
|
Sign up to set email alerts
|

Smouldering wildfires in peatlands, forests and the arctic: Challenges and perspectives

Abstract: Wildfires can be divided into two types, flaming or smouldering, depending on the dominant combustion processes. Both types are present in most wildfires, and despite being fundamentally different in chemical and physical terms, one transitions to the other. Traditionally, science has focused on flames, while smouldering is often misinterpreted. But smouldering wildfires are emerging as a global concern because they cause extensive air pollution, emit very large amounts of carbon, are difficult to detect and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 69 publications
(89 reference statements)
1
46
0
Order By: Relevance
“…Presence of charred and uncharred plant remains in multiple levels of the cores suggests (local) wildfires (for more information on (palaeo)wildfires in peatlands see e.g. Zaccone et al, 2014;Nelson et al, 2021;Rein and Huang, 2021). Dry periods allow further breakdown of material, which could explain the rather poor preservation of uncharred (waterlogged) macrofossils.…”
Section: Palaeoenvironmentmentioning
confidence: 99%
“…Presence of charred and uncharred plant remains in multiple levels of the cores suggests (local) wildfires (for more information on (palaeo)wildfires in peatlands see e.g. Zaccone et al, 2014;Nelson et al, 2021;Rein and Huang, 2021). Dry periods allow further breakdown of material, which could explain the rather poor preservation of uncharred (waterlogged) macrofossils.…”
Section: Palaeoenvironmentmentioning
confidence: 99%
“…However, this part of the organic carbon is not stable due to continued changes of the habitat conditions and smoldering after the fire, which likely could destroy these aggregates. Research has shown that underground fires, especially smoldering of underground biomass, can lead to further losses and destabilization of SOC [6,7].…”
Section: Variability Of Water Stable Soil Aggregates (Wsa) and Associated Soc (Wsa-soc) After Wildfirementioning
confidence: 99%
“…Boreal forest can also be a significant contributor to the atmospheric CO 2 from above and underground biomass burning [6]. A recent review [7] points to the importance of underground biomass burning (smoldering) as a significant contributor to atmospheric CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, peat can be flammable when dry or thawed and wildfires can be ignited by natural events such as lightning (Mickler et al 2017) and self-heating (Restuccia et al 2017), or anthropogenic activities such as land clearing, accidental burning, and arson (Page et al 2002(Page et al , 2011. Their spread is governed by smouldering combustion, and fires can last for weeks or months despite rainfall or firefighting (Page et al 2002;Huijnen et al 2016;Rein and Huang 2021) (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The recent 2015 haze episode in Southeast Asia released 227 ± 67 Tg of Carbon, with an average rate of daily CO 2 emission exceeding the fossil fuel emission rate of the European Union (Huijnen et al 2016). Annually, drained peatlands release ~5% of global anthropogenic greenhouse gas emissions (IUCN 2017), which, considering the very long period of 100-1000 years needed for the carbon in peatland to be stored, contribute to the acceleration of climate change (Kelly et al 2013;Rein 2013;Gandois et al 2019;Walker et al 2020;Rein and Huang 2021).…”
Section: Introductionmentioning
confidence: 99%